Genome-wide analysis of lectin receptor-like kinases in Populus. (December 2016) - Yang, Yongil; Labbé, Jessy; Muchero, Wellington; Yang, Xiaohan; Jawdy, Sara; Kennedy, Megan; Johnson, Jenifer; Sreedasyam, Avinash; Schmutz, Jeremy; Tuskan, Gerald; Chen, Jin-Gui
Abstract Background Receptor-like kinases (RLKs) belong to a large protein family with over 600 members in Arabidopsis and over 1000 in rice. Among RLKs, the lectin receptor-like kinases (LecRLKs) possess a characteristic extracellular carbohydrate-binding lectin domain and play important roles in plant development and innate immunity. There are 75 and 173 LecRLKs in Arabidopsis and rice, respectively. However, little is known about LecRLKs in perennial woody plants. Results Here we report the genome-wide analysis of classification, domain architecture and expression of LecRLKs in the perennial woody model plantPopulus . We found that the LecRLK family has expanded inPopulus to a total of 231, including 180 G-type, 50 L-type and 1 C-type LecRLKs. Expansion of thePopulus LecRLKs (PtLecRLKs) occurred partially through tandem duplication. Based on domain architecture and orientation features, we classified PtLecRLKs into eight different classes. RNA-seq-based transcriptomics analysis revealed diverse expression patterns ofPtLecRLK genes among leaves, stems, roots, buds and reproductive tissues and organs. Conclusions This study offers a comprehensive view of LecRLKs in the perennial woody model plantPopulus and provides a foundation for functional characterization of this important family of receptor-like kinases.